Toward a Global Political Sociology of School Choice Policies. Issue 1 (January 2020) - Lingard, Bob
This paper on the political sociology of school choice policies has been written as a supplement to the essays in the 2020 Politics of Education Association Yearbook and locates them in cognate literatures. In addition, the papers are situated against the changing political and global contexts of such policies, as global pressures, discourses, and policyscapes have been recently challenged to some extent by the rise of new nationalisms and ethno-nationalism in many nations across the globe. School choice policies are linked with practices of marketization, privatization, and commercialization and some conceptual clarification is proffered. Policy is defined as referring to processes, framing discourses, and specific texts. Statecraft (logics and working of the state) has been reconstituted by these changes, with one important often over-looked element of this craft being scalecraft (work creating the scales of policies), that is, policy work on constituting local, national, regional, and global relationships and scales.